2010
DOI: 10.1186/1471-2164-11-226
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparison between IL-17 and combined TNF-alpha/IL-17 induced genes in primary murine hepatocytes

Abstract: BackgroundCytokines such as TNF-alpha and IL-1beta are known for their contribution to inflammatory processes in liver. In contrast, the cytokine IL-17 has not yet been assigned a role in liver diseases. IL-17 can cooperate with TNF-alpha to induce a synergistic response on several target genes in different cell lines, but no data exist for primary hepatocytes. To enhance our knowledge on the impact of IL-17 alone and combined with TNF-alpha in primary murine hepatocytes a comprehensive microarray study was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 61 publications
3
36
0
1
Order By: Relevance
“…In fact, the simultaneous down-regulation of TNF, interleukin 1b (IL1B), the chemokine CXCL2, the immediate early genes IER3 and NFKBIZ is suggestive of a moderate anti-inflammatory response to the extended fast. Both TNF and IL1B are known to stimulate the expression of CXCL2, NFKBIZ and IER3 at the level of the gene transcripts in a variety of cells (Shen et al 2005;Sparna et al 2010). As reported previously, multiplex immunoassay analysis of plasma samples from the same subjects showed a small but significant reduction in circulating IL1B protein concentrations that parallels the change in PMBC IL1B mRNA levels observed here (Bouwman et al 2011).…”
Section: Effects Of Extended Fast On Pbmc Transcription Profilessupporting
confidence: 77%
“…In fact, the simultaneous down-regulation of TNF, interleukin 1b (IL1B), the chemokine CXCL2, the immediate early genes IER3 and NFKBIZ is suggestive of a moderate anti-inflammatory response to the extended fast. Both TNF and IL1B are known to stimulate the expression of CXCL2, NFKBIZ and IER3 at the level of the gene transcripts in a variety of cells (Shen et al 2005;Sparna et al 2010). As reported previously, multiplex immunoassay analysis of plasma samples from the same subjects showed a small but significant reduction in circulating IL1B protein concentrations that parallels the change in PMBC IL1B mRNA levels observed here (Bouwman et al 2011).…”
Section: Effects Of Extended Fast On Pbmc Transcription Profilessupporting
confidence: 77%
“…Th22 cells have been described as a new Th subset exclusively producing IL-22, but not IL-17 or IFNγ [17,18]. Consistent with a role of adaptive immunity in hepatic inflammation, NASH was found to be associated with a Th1 cytokine response characterized by IFNγ and TNFα secretion in mice [10,19], and genome-wide analysis showed that stimulation of primary hepatocytes with IL-17 induced the expression of several inflammation-associated genes, including chemokines and C-reactive protein [20]. Finally, adaptive immunity responses may directly affect different steps of NAFLD evolution towards more severe liver diseases.…”
mentioning
confidence: 88%
“…In primary hepatocytes, MCPIP1 mRNA is induced synergistically by TNF and IL-17 (10). Transcriptional induction by IL-1␤ has been demonstrated to involve the NF-B and ERK pathways and Elk-1 transcription factor (33,34).…”
mentioning
confidence: 99%
“…Marked synergy in induction of gene expression has been observed with other inflammatory stimuli, e.g. TNF (9,10) or poly(I:C) (11). The IL-17 family contains several isoforms that homo-or heterodimerize and bind to members of a distinct family of IL-17 receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation